Is English the Gateway or Gatekeeper? Exploring the Impact of English-Only Policies in Asia - Onoza, Hilda De Guzman; Pelila, John Rey Osben; Ngitew, Judy May Alcos; Santiago, Krisha Mecca Macasling; Castro, Louis Andrew Basilio (Papanda Publisher, 2025)
As far as studies on the English-only policy (EOP) are concerned, there is a notable concentration of research focusing on Asia. To better represent this region and gain a comprehensive understanding of how EOP is applied in diverse educational contexts, this study aims to examine the roles, benefits, challenges, and recommendations associated with EOP implementation in Asian schools. Through a systematic literature review, inclusion and exclusion criteria were applied, and 38 journal articles from the ERIC database covering 15 Asian countries were screened for review. The findings indicate that the role of EOP in education across Asian countries primarily centers on preparing students for international opportunities and addressing challenges in teacher training. The benefits of EOP implementation include improving language proficiency and enhancing student engagement. However, several challenges were identified, such as the marginalization of local languages and cultural education, excessive demands in enforcing EOP, and increased difficulties for students with limited English exposure. The review also presents several recommendations for strengthening and improving EOP in educational institutions: enhancing classroom practices, language strategies, and assessment; promoting cultural relevance, motivation, and engagement; developing communication strategies for effective language acquisition; supporting teacher training, curriculum development, and community involvement; and expanding EOP-related studies as a direction for future research. While EOP aligns with global standards by fostering English proficiency and cultural awareness and preparing students for globalization, it also presents significant challenges, including over-reliance on the English language, which can hinder learning and potentially alienate students who struggle with it. It is important to note that only 15 out of 49 Asian countries were represented in the review. This suggests a gap in the literature, as studies on EOP in the remaining countries are either limited or absent—highlighting a valuable area for future research.